2013
DOI: 10.1016/j.fct.2013.08.033
|View full text |Cite
|
Sign up to set email alerts
|

The methanolic extract of Cordyceps militaris (L.) Link fruiting body shows antioxidant, antibacterial, antifungal and antihuman tumor cell lines properties

Abstract: Being Cordyceps militaris (L.) Link recognized as a medicinal and edible mushroom, this work intends to reveal new interesting bioactive molecules that could be isolated from this species. Hydrophilic and lipophilic compounds were analysed by chromatographic techniques coupled to different detectors. The methanolic extract of C. militaris was tested for its antioxidant, antibacterial, antifungal and anti-proliferative properties in different human tumor cell lines. Mannitol (2.01 g/100 g dw) and trehalose (24.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 39 publications
2
78
0
1
Order By: Relevance
“…C. militaris has been used as an antioxidant for a long time. It has been confirmed that the extract of C. militaris could inhibit lipid peroxidation by scavenging free radicals [Reis et al 2013] and C. Sinensis could significantly improve the activity of SOD and GSH-Px to protect the testis from oxidative damage induced by cyclophosphamide in mice [Jin and Chen 2008]. These results suggested that C. militaris could alleviate BPA-induced oxidative damage.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…C. militaris has been used as an antioxidant for a long time. It has been confirmed that the extract of C. militaris could inhibit lipid peroxidation by scavenging free radicals [Reis et al 2013] and C. Sinensis could significantly improve the activity of SOD and GSH-Px to protect the testis from oxidative damage induced by cyclophosphamide in mice [Jin and Chen 2008]. These results suggested that C. militaris could alleviate BPA-induced oxidative damage.…”
Section: Discussionmentioning
confidence: 53%
“…Traditional Chinese medicine believes that C. militaris can be used to treat impotence, seminal emission, and infertility, and invigorate kidney and lungs [Ch 2000;Zhu et al 1998]. Pharmacological studies have confirmed that C. militaris possesses a wide range of biological activities including anti-bacterial, anti-tumor, anti-oxidation, and immune-modulatory [Liu et al 1994;Ng and Wang 2005;Reis et al 2013]. It can also improve reproductive function and repair reproductive dysfunction induced by cyclophosphamide in mice [Jin and Chen 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Organic acids were determined following a procedure previously described by the authors. 12,13 Analysis was performed using a Shimadzu 20A series UFLC (Shimadzu Corporation, Kyoto, Japan). Separation was achieved on an SphereClone (Phenomenex, Torrance, CA, USA) reverse phase C 18 column (5 µm, 250 mm × 4.6 mm i.d) thermostatted at 35 ºC.…”
Section: Hydrophilic Compoundsmentioning
confidence: 99%
“…Tocopherols were determined following a procedure previously described by the authors. 12,13 Analysis was performed by HPLC (equipment described above), and a fluorescence detector (FP-2020; Jasco) programmed for excitation at 290 nm and emission at 330 nm. The compounds were identified by chromatographic comparisons with authentic standards.…”
Section: Lipophilic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation